Mobile app for dissemination of medical information and tumour services - a case study of OOLH app in Lerdsin Hospital - Goh, Kian Liang; Piya, Kiatisevi; Bhasanan, Sukanthanak; Pongsiri, Piakong (2018)
Objective Tumour services is increasingly challenging due to rapid development of medical and surgical treatment. The internet and mobile technology play pivotal role in disseminating medical knowledge to our advantage as doctors and patients. To educate the technology-savvy patients, leveraging a smartphone app to deliver information regarding tumour services, knowledge and experience of each centre may be the cornerstone in providing a realistic overview of the expectant treatment that patients will receive. To achieve our objective, we developed a mobile app with the purpose of educating users regarding orthopaedic oncology and provide information regarding the services available in the Orthopaedic Oncology unit, Lerdsin Hospital, Thailand. Methods We developed a hybrid mobile app entitled Orthopaedic Oncology Lerdsin Hospital (OOLH) that runs on both iOS and Android platform. The app consists of information regarding overview of our hospital, unit, staff, speciality, services and programmes available, our experience in treating orthopedic tumours, list of research, publications, presentations, projects and innovations. The information is available in two languages,I.e., English and Thai. The app also allows users, specifically medical personnel, to communicate with our doctors regarding tumour cases via built-in social messaging. The app is available for free in the Apple AppStore and Google Play. Results Since the inception of this app, we believe our services are more widely made known to the public especially patients around Thailand. We expect increased awareness regarding sarcomas amongst the public, patients as well as medical personnel and hope for earlier referral for prompt and specialised treatment. Conclusions Mobile app is an engaging and modern platform for delivery of medical knowledge. Provision of essential information and instantaneous communication via mobile app may hopefully result in a better-informed society with timely and optimised patient care.